Expert System for Detecting Web-Based Respiratory Tract Infections at the Kalideres District Health Center - Rahmat Tullah; Fiqih Hana Saputri; Ryan Prasetya (Institut Teknologi dan Bisnis Bina Sarana Global, 2022)
The use of technology in the field of health is used to improve better health services. One of the implementations in the field of health is an expert system for diagnosing diseases. In Kalideres District Health Center, Respiratory Infection Disease (ISPA) became the category of 10 most cases of disease. ISPA disease management requires high awareness from both the public and health officials, especially about some factors that affect the degree of health. To overcome this, Kalideres District Health Center needs a system that can provide information in detecting ISPA disease that can provide the results of disease consultation. This is a good choice to solve the problem. In this stage the expert system for detecting ISPA disease-based websites is designed using PHP programming language and MySql database. This system has been run in the research place running well and effectively, as evidenced by testing Software Quality Assurance with a score of 84.8. it is expected that this expert system can handle the most cases of disease in Kalideres District Health Center.